Infrared spectroscopy of gas-phase M(+)(CO2)n (M = Co, Rh, Ir) ion-molecule complexes - Iskra, A; Gentleman, A; Kartouzian, A; Kent, M; Sharp, A; Mackenzie, S (American Chemical Society, 2016)
The structures of gas-phase M(+)(CO2)n (M = Co, Rh, Ir; n = 2-15) ion-molecule complexes have been investigated using a combination of infrared resonance-enhanced photodissociation (IR-REPD) spectroscopy and density functional theory. The results provide insight into fundamental metal ion-CO2 interactions, highlighting the trends with increasing ligand number and with different group 9 ions. Spectra have been recorded in the region of the CO2 asymmetric stretch around 2350 cm(-1) using the inert messenger technique and their interpretation has been aided by comparison with simulated infrared spectra of calculated low-energy isomeric structures. All vibrational bands in the smaller complexes are blue-shifted relative to the asymmetric stretch in free CO2, consistent with direct binding to the metal center dominated by charge-quadrupole interactions. For all three metal ions, a core [M(+)(CO2)2] structure is identified to which subsequent ligands are less strongly bound. No evidence is observed in this size regime for complete activation or insertion reactions.